A link between central kynurenine metabolism and bone strength in rats with chronic kidney disease - Kalaska,Bartlomiej; Pawlak,Krystyna; Oksztulska-Kolanek,Ewa; Domaniewski,Tomasz; Znorko,Beata; Karbowska,Malgorzata; Citkowska,Aleksandra; Rogalska,Joanna; Roszczenko,Alicja; Brzoska,Malgorzata M.; Pawlak,Dariusz (PeerJ, 2017)
Background Disturbances in mineral and bone metabolism represent one of the most complex complications of chronic kidney disease (CKD). Serotonin, a monoamine synthesized from tryptophan, may play a potential role in bone metabolism. Brain-derived serotonin exerts a positive effect on the bone structure by limiting bone resorption and enhancing bone formation. Tryptophan is the precursor not only to the serotonin but also and primarily to kynurenine metabolites. The ultimate aim of the present study was to determine the association between central kynurenine metabolism and biomechanical as well as geometrical properties of bone in the experimental model of the early stage of CKD. Methods Thirty-three Wistar rats were randomly divided into two groups (sham-operated and subtotal nephrectomized animals). Three months after surgery, serum samples were obtained for the determination of biochemical parameters, bone turnover biomarkers, and kynurenine pathway metabolites; tibias were collected for bone biomechanical, bone geometrical, and bone mass density analysis; brains were removed and divided into five regions for the determination of kynurenine pathway metabolites. Results Subtotal nephrectomized rats presented higher serum concentrations of creatinine, urea nitrogen, and parathyroid hormone, and developed hypocalcemia. Several biomechanical and geometrical parameters were significantly elevated in rats with experimentally induced CKD. Subtotal nephrectomized rats presented significantly higher kynurenine concentrations and kynurenine/tryptophan ratio and significantly lower tryptophan levels in all studied parts of the brain. Kynurenine in the frontal cortex and tryptophan in the hypothalamus and striatum correlated positively with the main parameters of bone biomechanics and bone geometry. Discussion In addition to the complex mineral, hormone, and metabolite changes, intensified central kynurenine turnover may play an important role in the development of bone changes in the course of CKD.
Keywords: Bone disorders; Chronic kidney disease; Kynurenine pathway; Brain